ANALISIS BIAYA PASCA PANEN DAN NILAI TAMBAH PENGGILINGAN PADI DI KOTA TERPADU MANDIRI KABUPATEN MESUJI - Ahmad Hafidz Afif Furqoni; Dwi Haryono; Sumaryo Gitosaputro (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to determine post-harvest handling and the amount of post-harvest costs and to analyze the added value of the rice milling business in the Independent Integrated City of Mesuji. The research method used a survey method. The study was conducted in the villages of Tanjung Mas Mulya, Tanjung Mas Makmur, and Pangkal Mas Mulya, East Mesuji Sub-District. The samples of this research were farmers and agro-industries. The number of samples were 37 farmers in Tanjung Mas Mulya Village, 22 farmers in Pangkal Mas Mulya Village, and 9 farmers in Tanjung Mas Makmur Village, while the samples from agro-industries were 5 owners from Tanjung Mas Mulya Village, 4 from Pangkal Mas Mulya Village, and 2 from Tanjung Mas Makmur Village.  Data collection was conducted from June to July 2019. The study results show that post-harvest handling by farmers was limited to transportation. The amount of harvest cost and post-harvest cost is IDR3,513,359.97 per hectare. The average value added in agro-industries using box dryer machines was IDR629.97 per kilogram of raw materials and IDR525.68 per kilogram of raw materials for agro-industries not using box dryer machines. Key words : added value, post harvest, rice milling